Dinamika geopolitik indo-pasifik: Strategi indonesia dalam menjaga keseimbangan kekuatan kawasan - Fakhirah, Laylla (Maliki Interdisciplinary Journal, 2025)
The Indo-Pacific region has transformed into the geopolitical center of gravity of the world, where the rivalry between the United States and China is becoming increasingly prominent. Within this landscape, Indonesia holds a central position, determined not only by its strategic geographic location but also by its diplomatic capabilities and adaptive foreign policy. This study aims to identify and analyze Indonesia’s strategies in responding to the geopolitical dynamics of the Indo-Pacific region. Using a qualitative-descriptive approach based on literature review, this article explores Indonesia’s role through the frameworks of classical geopolitics, critical geopolitics, and the complexity of interdependence. The analysis reveals that Indonesia upholds the principle of a free and active foreign policy, strengthens the Global Maritime Fulcrum initiative, and promotes multilateral diplomacy through the ASEAN Outlook on the Indo-Pacific (AOIP). These findings affirm that Indonesia strives to play the role of a mediator and balancer in maintaining a regional security architecture that is inclusive, stable, and free from conflict.